2020
DOI: 10.1002/bab.1941
|View full text |Cite
|
Sign up to set email alerts
|

Screening and molecular characterization of new thermo‐ and ethanol‐tolerant Acetobacter malorum strains isolated from two biomes Moroccan cactus fruits

Abstract: Industrially, the sensitivity of acetic acid bacteria (AAB) to the high temperatures and the high ethanol concentrations is the major concerns for manufacturers. This study was conceived and designed to isolate and identify new thermo-and ethanol-tolerant AAB from Opuntia ficus-indica L. fruits. As a result, among 140 isolated bacterial strains, five selected strains (CR1, CR5, CR23, CZ2, and CZ15) exhibited important acetic acid production until 40°C. The use of 16S rDNA gene analysis was insufficient to iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 46 publications
1
14
0
Order By: Relevance
“…Contrariwise, at 37 • C none of these bacteria strains or combinations of strains produced high concentrations of acetic acid, so that the acetobacter strains, the gluconobacter strains and the mixed strains obtained from Sherry vinegar achieved similar concentrations of just 1.88, 1.90 and 1.89 g/100 mL, respectively. Several reasons could explain this lower productivity, such as the effect of the high temperature on the viability of the acetic acid bacteria even if the two genera displayed thermotolerant characteristics in a previous study [32]. Other reasons could be the greater evaporation of ethanol during the fermentation at the highest temperature or a poor tolerance to a large ethanol concentration in the wine (8.7%) when at a high temperature.…”
Section: Vinegar Productionmentioning
confidence: 85%
See 3 more Smart Citations
“…Contrariwise, at 37 • C none of these bacteria strains or combinations of strains produced high concentrations of acetic acid, so that the acetobacter strains, the gluconobacter strains and the mixed strains obtained from Sherry vinegar achieved similar concentrations of just 1.88, 1.90 and 1.89 g/100 mL, respectively. Several reasons could explain this lower productivity, such as the effect of the high temperature on the viability of the acetic acid bacteria even if the two genera displayed thermotolerant characteristics in a previous study [32]. Other reasons could be the greater evaporation of ethanol during the fermentation at the highest temperature or a poor tolerance to a large ethanol concentration in the wine (8.7%) when at a high temperature.…”
Section: Vinegar Productionmentioning
confidence: 85%
“…The experiments were conducted at 30 • C and 37 • C in duplicate and the flasks were not agitated to allow the atmospheric oxygen to diffuse slowly into the fermenting medium. A temperature of 37 • C showed the best results in terms of production of acetic acid by thermotolerant bacteria in a previous work [32] and it was compared with the usual acetification temperature (30 • C). The content in each flask was sampled every three weeks and each sample's total acidity was determined by titration with NaOH using phenolphthalein indicator.…”
Section: Surface Culture Acetificationmentioning
confidence: 95%
See 2 more Smart Citations
“…Perumpuli et al reported that A. pasteurianus SL13E-2, SL13E-3, and SL13E-4 produced more than 40 g/L of acetic acid at 37 °C, an ethanol concentration of 46.58 g/L, and at 200 rpm [ 23 ]. Es-sbata et al reported that A. malorum strains produced more than 40 g/L of acetic acid at 37 °C [ 24 ]. Kadere et al isolated several Acetobacter and Gluconobacter strains.…”
Section: Resultsmentioning
confidence: 99%